Prevalence and Predictors of Contraceptive Use Among Women of Premenopausal Period in Ethiopia: A Retrospective Cross-Sectional Data Analysis - Geleta D; Kebede A; Bulcha G; Usman H; Hajibediru K; kebede S; Dubale S; Degu G (Dove Medical Press, 2021)
Daniel Geleta,1 Abebe Kebede,2 Gebeyehu Bulcha,3 Hyder Usman,2 Kunuz Hajibediru,4 Selass kebede,2 Sileshi Dubale,2 Getu Degu5 1Tropical & Infectious Diseases, Jimma University, Jimma, Oromia, Ethiopia; 2Pharmaceutical science, Jimma University, Jimma, Oromia, Ethiopia; 3Health Communication and Health Behavior, Jimma University, Oromia, Ethiopia; 4Reproductive Health,Jimma University, Jimma, Oromia, Ethiopia; 5Epidemiology and Biostatistics, Bahir Dar University, Bahir Dar, Amhara, EthiopiaCorrespondence: Daniel Geleta P.O.Box: 378 Tel +125 911723400Fax +251 471111450; +251 471112040Email daninagaa2009@gmail.comBackground: Contraceptive use is internationally endorsed as a human right and an indicator of the highest standard of sexual and reproductive health life. But reports from countries including Ethiopia showed a lower and capricious rate due to wider factors. Thus, the current study aimed to determine the prevalence and the predictors of contraceptive use among women of the premenopausal period.Methods: A retrospective cross-sectional data analysis was performed from Ethiopian Demographic and Health survey 2019 in January 2021. A total of 3260 premenopausal women were included by stratified sampling, and data were analyzed using SPSS version 25 software. Data were initially analyzed descriptively, and tests were done for variable multicollinearity, and model goodness of fit and predictive capacity. Subsequently, bivariate and multivariable logistic regression analyses were performed successively for the crude and adjusted odds ratio, and finally declared variables with a p-value of < 0.05 as predictors of contraceptive use.Results: The study included 3260 women with an average age of 41.66 (standard deviation ± 3.9) years. The overall prevalence of contraceptive use was reported 17% and explained to vary by women's age, place of residence, education level, wealth index, and current working statuses. However, only the age, education, and wealth index of women have predicted a statistical significance with contraceptive use. Accordingly, an increase in women's age was found to increase contraceptive use more likely by 89% [AOR=0.89 (95% CI: 0.87, 0.92)]. Similarly, primary [AOR = 1.53, (95% CI: 1.20, 195)], secondary [AOR = 2.57, (95% CI: 1.70)] or higher [AOR = 2.64, (95% CI: 1.67, 4.20)] level educated women were about twice more likely to use contraceptive methods than uneducated women. Finally, women in poorer [AOR = 3.11 (95% CI: 2.17, 4.46)], middle [AOR = 3.03 (95% CI: 2.09, 4, 37)], rich [AOR = 3.70, (95% CI: 2.58, 5.31)] or richest [AOR = 3.42, (95% CI: 2.39, 4, 88)] wealth index were more than 3 times more likely use contraceptive methods when compared to women of the poorest wealth index.Conclusion: The prevalence of contraceptive use among premenopausal women in Ethiopia is low and utmost related to age, education level, and wealth index of women.Keywords: contraceptive, predictors, premenopausal, prevalence, women